(untitled) (Dentika: Dental Journal, 2009)
A basic material of polymethyl methacrylate (PMMA) acrylic resins is methyl methacrylate (MMA) monomer and widely used in dental medicine. It is primarily used for removable orthodontic, partial and full denture appliances, and also for dental fillings. The facts and results of the previous studies showed that MMA might act as irritant in certain concentration, and also as immunogen or allergen. This study examined the immunopathogenesis of oral mucosal tissue destruction in patients exposed to MMA, by detecting the concentrations of plasma IL-4, IFN-Î³, TNF-Î±, serum IgG and IgE specific to MMA that mediated irritation and allergic reactions. The general objective of this research was to examine the immunopathogenesis of oral mucosal tissue destruction in patients exposed to MMA. The study used observasional case control study design. Laboratory tests for all samples were assessing plasma IL-4, IFN-Î³ and TNF-Î± using direct sandwich ELISA technique. Serum IgG and IgE specific to MMA were assessed by indirect ELISA. It was concluded that MMA is immunogenic in patients exposed to MMA that can induce IgG anti-MMA. Furthermore, this study also proved that immunopathogenesis of oral mucosal tissue destruction in patients exposed to MMA did occur through irritation and type I hypersensitivity reaction mediated by IgE, but occurred through type IV hypersensitivity reactions.